2022
DOI: 10.1371/journal.pone.0273919
|View full text |Cite
|
Sign up to set email alerts
|

Changes in physical activity and sedentary time in United States adults in response to COVID-19

Abstract: Physical activity is associated lower risk for a broad range of non-communicable diseases and early mortality, and even small changes in daily activity levels could have a profound effect on public health at the population level. The COVID-19 pandemic reshaped daily life for United States (US) adults resulting in reductions in physical activity early in the pandemic, but its longer-term effects on daily activities are unknown. To examine the longer-term impact of the pandemic on daily activity levels, we condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Some studies have found that certain individuals in the U.S. who started working from home after the onset of the pandemic spent more time eating than on-site workers (Pabilonia & Vernon, 2022;Restrepo & Zeballos, 2020). Meanwhile, multiple studies have found no significant changes in physical exercise among U.S. adults during the pandemic (Cowan, 2023;Matthews et al, 2022). Given our mixed results for searches related to healthy habits, we can at best speculate that the observed post-lockdown weight gain might not be primarily due to a decrease in physical exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that certain individuals in the U.S. who started working from home after the onset of the pandemic spent more time eating than on-site workers (Pabilonia & Vernon, 2022;Restrepo & Zeballos, 2020). Meanwhile, multiple studies have found no significant changes in physical exercise among U.S. adults during the pandemic (Cowan, 2023;Matthews et al, 2022). Given our mixed results for searches related to healthy habits, we can at best speculate that the observed post-lockdown weight gain might not be primarily due to a decrease in physical exercise.…”
Section: Discussionmentioning
confidence: 99%
“…As seen in previous studies, shortterm impacts of these stay-at-home orders included changes in day-to-day life, resulting in reduced physical activity and increased sedentary behavior. 12,13 Mental health challenges and stress due to the COVID-19 pandemic led to increases in risky dietary behaviors associated with weight gain, such as stress eating and increased alcohol consumption. 14,15 There is a critical need for evidence on changes in health outcomes using large sample data with an accurately measured COVID-19 pandemic timeframe.…”
Section: Introductionmentioning
confidence: 99%